The Effect of Sodium Bicarbonate Added To Water On First Class Soccer Players' Pulse After Effort - Jawad Kadhim, Mohammed; ALWEE ZAQIR, Ahmed (Journal of Physical Education, 2018)
The Effect of Sodium Bicarbonate Added To Water On First Class Soccer Players' Pulse After EffortThe importance of the research lies in identifying the effect of taking sodium bicarbonate on pulse after effort in first class soccer players. The problem of the research lies in the lack of interest in fluids given to athletes that plays an integral role in recovery and fluid lose replacement. The researcher aimed at identifying the effect of sodium bicarbonate added to water after effort. The researcher used the experimental method. The subjects were (7) first class soccer players from science and technology club. They were tested using VO2max then a pilot study was conducted on two players followed by the main test 12 – 19/3/2014. The data was collected and treated using proper statistical operations to conclude that taking sodium bicarbonate added to water increases the athletes' ability to endure effort for a long time. The researcher recommended using sodium bicarbonate in water before matches to increase pulse endurance after effort.